Variation in lipid mediator and cytokine levels during mouse femur fracture healing. Issue 11 (14th March 2016) - Lin, Hsuan‐Ni; Cottrell, Jessica; O'Connor, J. Patrick
ABSTRACT: Fracture healing is regulated by a variety of inflammatory mediators and growth factors which act over time to regenerate the injured tissue. This study used a mouse femur fracture model to quantify the temporal expression pattern of lipid mediators, cytokines, and related mRNAs during healing. Cyclooxygenase (COX‐1 and COX‐2) and 5‐lipoxygenase (5‐LO) derived lipid mediators, cytokines, and mRNA levels were quantified using mass spectrometry (LC‐MS/MS), bead‐based multiplex assays (xMAP), and quantitative PCR of cDNA (RTqPCR), respectively. Our analysis found that, the early inflammatory response (between 0 and 4 days after fracture) in the mouse femur fracture model coincided with elevated levels of COX‐derived lipid mediators and inflammatory cytokines but with decreased levels of 5‐LO‐derived lipid mediators. Further, the COX‐derived lipid mediators remained elevated for at least 7 days after fracture, suggesting that the COX‐derived lipid mediators have additional functions during later phases of the fracture healing response. Differences were also found between mRNA levels and corresponding cytokines and lipid mediator levels, supporting a role for post‐transcriptional regulation of gene expression. The temporal changes in fracture callus lipid mediator levels and inflammatory cytokines support a general positive role for inflammatory cytokines and COX‐derived lipid mediators on fracture healing and a general negative role for 5‐lipoxygenase derived lipid mediators during the initial stages of repair. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1883–1893, 2016.